Partisan social happiness - Rafael DiTella; Robert MacCulloch (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
We use data on the subjective well-being of more than a quarter of a million people living in the OECD over the period 1975-92 to study the behavior of partisan social happiness functions. Controlling for personal characteristics of the respondents, year and country fixed effects and country specific time trends, we find that the data describe social happiness functions for left-wing and right-wing individuals where inflation and unemployment enter negatively. We use these functions to test the root assumption of partisan business cycle models where leftwing individuals care more about unemployment relative to inflation than rightwingers (e.g. Alesina (1987)). Bootstrap confidence intervals suggest that up to 90 per cent of the time the evidence is consistent with this assumption. We also find that left-wingers like increases in government consumption more than rightwingers, that the latter have become more concerned with inflation over time and that the poor (rich) behave differently from the left (right). Finally, we find that individuals declare themselves to be happier when the party they support is in power, even after controlling for economic variables. Our findings are hard to explain using median voter models but are to be expected in a partisan world.
Keywords: E6; 330; Median voter; partisan business cycles; subjective well-being; Lebensqualität; Arbeitslosigkeit; Inflationsrate; Einkommen; Schätzung; Politischer Konjunkturzyklus